-x + 7 = x - 5
add x to both sides of the equation
7 = 2x - 5
add 5 to both sides of the equation
12 = 2x
divide 2 from both sides of the equation
6 = x
-6x^2+4x
my reasoning:
eliminate the opposites (5 & -5)
collect the like terms (-8x^2 & + 2x^2)
collect the like terms again (-3x &+7x)
Answer:
help u with what? Say what u need
The lateral area of the prism equals to height * perimeter of the base. So the lateral area is 160 cm2. And the surface area of the prism equals to the area of the base*2+the lateral area= 202 cm2.
<u>Answer:</u>
one solution = 3
<u>Step-by-step explanation:</u>
Let's solve your equation step-by-step.
5x+17=4(3x−1)
Step 1: Simplify both sides of the equation.
5x+17=4(3x−1)
5x+17=(4)(3x)+(4)(−1)(Distribute)
5x+17=12x+−4
5x+17=12x−4
Step 2: Subtract 12x from both sides.
5x+17−12x=12x−4−12x
−7x+17=−4
Step 3: Subtract 17 from both sides.
−7x+17−17=−4−17
−7x=−21
Step 4: Divide both sides by -7
-7x/-7 = -21/-7 = 3